2004
DOI: 10.1074/jbc.m401022200
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome α-Subunit XAPC7 Interacts Specifically with Rab7 and Late Endosomes

Abstract: Rab7 is a key regulatory protein governing early to late endocytic membrane transport. In this study the proteasome ␣-subunit XAPC7 (also known as PSMA7, RC6 -1, and HSPC in mammals) was identified to interact specifically with Rab7 and was recruited to multivesicular late endosomes through this interaction. The protein interaction domains were localized to the C terminus of XAPC7 and the N terminus of Rab7. XAPC7 was not found on early or recycling endosomes, but could be recruited to recycling endosomes by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 62 publications
4
50
0
Order By: Relevance
“…The mechanism by which this occurs appears unclear, because the proteasome is generally considered to be cytosolic and A␤ 42 accumulates in the inner side of, or within, the outer membrane of MVBs. However, A␤ 42 was reported to inhibit proteasome function in vitro (Gregori et al, 1995(Gregori et al, , 1997 and a direct interaction between the ␣-subunit XAPC7 of the proteasome to MVB/late endosomes was recently described (Dong et al, 2004). Moreover, by immunoelectron microscopy, we observed that the ␤-subunit of the 20S proteasome localizes to MVBs in neurons of the brain.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The mechanism by which this occurs appears unclear, because the proteasome is generally considered to be cytosolic and A␤ 42 accumulates in the inner side of, or within, the outer membrane of MVBs. However, A␤ 42 was reported to inhibit proteasome function in vitro (Gregori et al, 1995(Gregori et al, , 1997 and a direct interaction between the ␣-subunit XAPC7 of the proteasome to MVB/late endosomes was recently described (Dong et al, 2004). Moreover, by immunoelectron microscopy, we observed that the ␤-subunit of the 20S proteasome localizes to MVBs in neurons of the brain.…”
Section: Discussionmentioning
confidence: 49%
“…Localization of a proteasome subunit (XAPC7) to late endosomal membranes was recently described in BHK21 cells (Dong et al, 2004). To investigate whether proteasomes also localize to membrane compartments in neurons of the brain, we performed immuno-EM using an antibody against the 20S subunit of the proteasome (Fig.…”
Section: A␤ Accumulation In App Mutant Neurons Reduces Proteasome Actmentioning
confidence: 99%
“…5, G and H). Recently, a new connection between the proteasome and membrane traffic has been established with the discovery that a proteasome ␣-subunit (XAPC7/PSMA7/HSPC) interacts with Rab7 on multivesicular bodies and that overexpression of this subunit interferes with the transport of membrane proteins from early to late endosomes (46). Exactly how proteasome inhibitors affect this interaction and thereby alter subcellular trafficking remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Homology-based genome-wide search of the putative effectors of the amoebic Rab7A using known Rab7 effectors from other organisms, including RILP, Rabring7, hVps34p/p150 (phosphatidylinositol 3-kinase), and proteasome ␣-subunit (XAPC7) indicated that this organism possesses homologues for Vps34/p150 and XAPC7, but lacks RILP and Rabring7, suggestive of the presence of novel Rab7 effectors in this organism (Cantalupo et al, 2001;Mizuno et al, 2003;Stein et al, 2003;Dong et al, 2004). Thus, we attempted to isolate the effector molecules of EhRab7A by affinity purification to gain an insight in the regulation of the amoebic Rab7A.…”
Section: Identification Of a Retromerlike Complex As A Novel Ehrab7a mentioning
confidence: 99%